An all-lignin-based flexible supercapacitor based on a nitrogen-doped carbon dot functionalized graphene hydrogel. (12th November 2021) - Cui, Linlin; An, Yingrui; Xu, Hanping; Jia, Mengying; Li, Yue; Jin, Xiaojuan
Abstract : In this manuscript, the synthesis of a nitrogen-doped carbon dot functionalized graphene hydrogel and its application as a supercapacitor electrode have been reported. Abstract : Designing flexible supercapacitors (FSCs) as energy storage devices for portable/wearable electronic products using the earth-abundant, renewable and environmentally friendly natural biomass has the prospect of building a green, sustainable society. Here, we report a new type of three-dimensional graphene hydrogel with lignin-based nitrogen-doped carbon dots as a decorative material. The nitrogen doped carbon dots are anchored in a graphene sheet through π–π bonds and electrostatic interactions, forming a stable three-dimensional network structure, which comprehensively improves the electrochemical performance of the electrode material. As an electrode, the specific capacitance reaches 387 F g −1 at 1 A g −1, and the rate performance reaches 75.7% when the current density increases to 7 A g −1 . In addition, an all-lignin-based supercapacitor assembled with a lignin hydrogel as the electrolyte has superior cycle stability (cycle life after 5000 cycles is 92.3%) and rate performance. When the power density is 243 W kg −1, the energy density is 25.6 W h kg −1 ; moreover, the FSC has excellent electrochemical stability even at different bending angles. This all-lignin-based FSC with excellent electrochemical performance and flexibility opens up a new path for the application of lignin in flexible energy storage devices.